LEGAL ANALYSIS ON DELIBERATE TAX EVASION IN INDONESIA - Adeh Dwi Putra; Imran Eka Saputra; Muhammad Djaelani Prasetya; Ali Rahman (Jurnal Meta-Yuridis, 2023)
This study aims to analyze the crime of deliberately not paying taxes that have been withheld or collected (Tax Evasion) in Indonesia. This study uses normative legal research with a statutory approach (statute approach) and a case approach (statute approach). In this study, legal materials were analyzed qualitatively with steps, namely (1) identifying legal facts and eliminating irrelevant matters; (2) collecting legal and non-legal materials; (3) conducting a review of legal issues; (4) drawing conclusions and providing prescriptions.The results of the study show that First, the general description includes the indictment, demands, witness statements, and expert statements. Second, in the analysis of facts, there are differences between public prosecutors and legal advisors specifically in calculating losses to state revenues, and thirdly, in the juridical analysis, there are differences in the application of legislation where the application of administrative penal law and ultimum remedium is not yet achieved